Experimental and numerical research on the axial and radial concentration distribution feature of miscible fluid interfacial mixing process in products pipeline for industrial applications. (December 2018) - He, Guoxi; Lin, Mohan; Wang, Baoying; Liang, Yongtu; Huang, Qiyu
Highlights: An experimental loop for sequential transportation is designed and implemented. The radial and axial features of concentration distribution are figured out. The tailing phenomenon is found, simulated and analyzed. New models for simulating concentration and dimensionless indices are proposed. Abstract: During the process of sequential transportation of miscible but dissimilar fluid (MBDF) in pipelines, the adjacent of different kinds of MBDF will be mixed, leading to form a section of a liquid mixed segment in the pipeline which is an important aspect of mass transfer, especially in the multiproduct pipeline. This paper represents an experimental study of sequential transportation of MBDF in a single pipeline and thereby a set of experimental loop platform for sequential transportation has been designed. Several dimensionless indices including mixed segment length, axial tailing length, and radial difference have been proposed to measure the concentration distribution in the mixed segment (CDMS) in both axial and radial directions of a pipeline. A novel numerical model to simulate the CDMS of MBDF transported in a pipeline is also proposed and solved, where the turbulence effect, the difference in physical properties of the front and tail fluid, and the adsorption effect are taken into account to investigate the diffusion coefficient and concentration distribution. The complex flow and mass transfer in transportation process can be observed in the experiment and the results illustrate that the concentration profile is asymmetrical respect to the 50% concentration point at different time and distance, which is not revealed in the solutions of existing both numerical theory and empirical formula. The simulated results figure out the radial and axial feature of CDMS and achieve a good agreement with the experimental length of the mixed segment. Thus, the tailing phenomenon is found, analyzed and simulated. Those mentioned-above 3 kinds of effects are considered to form the tailing phenomenon in CDMS interactively. The overall uncertainty of the proposed dimensionless parameters has also been analyzed. The results reveal that the length of the tail of the mixed segment (LTMS) is 22% longer than that of the front (LFMS) when taking the 5% change of concentration as the judging criteria. The detection probe located at the center of the pipe earliest detects the CDMS while the probe near the pipe wall does latest. The corresponding detection time difference is up to 25.64%. Finally, the research results can provide guidance for delivering the refined oils sequentially and cutting the mixed segment in the industrial pipelines.